Persepsi dan Perilaku Konsumen Bisnis terhadap Daging Sapi Beku, Studi Kasus: DKI Jakarta, Indonesia - A. Apriantini; I. I. Arief; L. Cyrilla ENSD; S. Riyanto; R. Adiyoga (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
The perception and purchase behavior to frozen beef from 90 Business consumers in Jakarta,Indonesia were evaluated. Respondents were interviewed face-to-face by a structured questionnaire.The questionnaire was divided into three parts, first part about characteristic of respondents, secondpart about purchasing behavior, and the last part about respondents’ perceptions toward frozen beef.Moreover, the relationship between perceptions and consumer characteristics of frozen beef wasanalyzed. Business consumers in the DKI Jakarta had a good perception of frozen beef. The aspectof product quality had the lowest score and price aspect had the highest score. Business scale had asignificant relationship with consumer perceptions (P<0.05). This result showed that the larger of thebusiness scale cause the better perception of business consumers towards frozen beef. The amount ofbeef consumption per month had a significant relationship (P<0.05) and in line with the level of businessconsumers’ perceptions of frozen beef. This result showed a significant relationship between the levelof consumer perception and the amount of beef consumption per month. the high beef consumptioncause the better the consumer’s perception of frozen beef. The increasing consumption indicates that therespondents had a good perception.